Tle6 deficiency in male mice led to abnormal sperm morphology and reduced sperm motility - Kazama, Kousuke; Miyagoshi, Yuki; Nishizono, Hirofumi (Frontiers in Cell and Developmental Biology, 2024)
Infertility affects over 15% of the global population, and genetic mutations are a substantial cause of infertility. Recent studies have focused on the subcortical maternal complex and its role in early embryonic development. TLE6, a core protein in the subcortical maternal complex, is crucial for female fertility; however, its role in male germ cells remains poorly understood. In this study, we generated a novel Tle6 knockout mouse model using CRISPR-Cas9 to examine the impact of Tle6 mutations on male fertility. Tle6 knockout males exhibited a reduced total sperm count compared to wild-type mice, with a marked decrease in highly motile sperm. Histological observation of Tle6 +/- mouse testes showed no apparent structural changes, though impaired sperm maturation was observed. Immunofluorescence staining showed that TLE6 localizes to the midpiece of sperm. It was also confirmed that the expression of Tle6 is reduced in Tle6 +/-male mice. In addition, Tle6 +/-mice exhibited a significant increase in serum testosterone levels compared to wild-type mice. Changes in the expression of genes related to sperm function were also observed in the testes of Tle6 knockout mice. These findings suggest that TLE6 is involved in sperm production and function, and that mutations in TLE6 may impair the production of functional sperm in humans, potentially leading to infertility.